Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Sales Growth dan Kualitas Audit terhadap Tax Avoidance - Tri Wahyuni; Djoko Wahyudi (Universitas Sains dan Teknologi Komputer, 2021)
Taxes becomes very important because taxes provide a large contribution to state revenues. This study aims to analyze the influence of profitability, leverage, firm size, sales growth dan audit quality to tax avoidance. The sample of this study were Indonesia Stock Exchange registered manufacture companies in 2017 until 2019 thus 213 data were used in this study. descriptive statistical test and multiple regression tests with the SPSS 26 were used to analyze the data. This study showed that the independent variabel profitability has a significant positive effect on tax avoidance, leverage has a significant negative on tax avoidance. On the other hand, firm size, sales growth and audit quality does not affect the tax avoidance variable